(untitled) (Jornal Memorial da Medicina, 2022)
A rare case of bilateral abducens nerve palsy occurred in a 60-year-old man hospitalized after a sudden severe headache and horizontal binocular diplopia. The patient did not present other neurological manifestations. A computed tomography (CT) revealed a subarachnoid hemorrhage, and the arteriography showed an anterior communicating artery (ACoA) aneurysm. After the aneurysm embolization, the patient continues to evolve with maintenance of the condition. Bilateral abducens nerve palsy can occur due to several factors, but its pathophysiology associated with the rupture of aneurysms in ACoA has several gaps in knowledge and scarce literary support. Thus, the need for studies in this field is pointed.